Characterization of the starch molecular structure of wheat varying in the content of resistant starch - Xingchen Liu; Liang Qiao; Yixi Kong; Huiyutang Wang; Baoju Yang (Food Chemistry: X, 2024)
Resistant starch (RS) is the total amount of starch that is incompletely or not digested and absorbed in the small intestine. It plays a role similar to dietary fibre with beneficial effects for human health. In this study, the RS content of 129 wheat accessions was determined, and the relationship between the several starch physical properties and resistant starch content were analyzed. By comparing the total starch content, amylose starch content, starch chain length distribution, starch crystallization type, starch branching degree, and starch granule morphology between the high RS and low RS content wheat accessions, it was found that the amylose content and RS content were significantly positively correlated. However, in the range of chain length fb 3 (DP ≥ 37), there was a significant negative correlation between amylopectin content and RS content. The surface of starch granules became increasingly smooth as the content of RS increased.